Mutations in DNAH5 account for only 15% of a non-preselected cohort of patients with primary ciliary dyskinesia. Issue 4 (8th April 2009) - Failly, M; Bartoloni, L; Letourneau, A; Munoz, A; Falconnet, E; Rossier, C; de Santi, M M; Santamaria, F; Sacco, O; DeLozier-Blanchet, C D; Lazor, R; Blouin, J-L
Abstract : Background: Primary ciliary dyskinesia (PCD) is characterised by recurrent infections of the upper respiratory airways (nose, bronchi, and frontal sinuses) and randomisation of left–right body asymmetry. To date, PCD is mainly described with autosomal recessive inheritance and mutations have been found in five genes: the dynein arm protein subunits DNAI1, DNAH5 and DNAH11, the kinase TXNDC3, and the X-linked retinitis pigmentosa GTPase regulator RPGR . Methods: We screened 89 unrelated individuals with PCD for mutations in the coding and splice site regions of the gene DNAH5 by denaturing high performance liquid chromatography (DHPLC) and sequencing. Patients were mainly of European origin and were recruited without any phenotypic preselection. Results: We identified 18 novel (nonsense, splicing, small deletion and missense) and six previously described mutations. Interestingly, these DNAH5 mutations were mainly associated with outer + inner dyneins arm ultrastructural defects (50%). Conclusion: Overall, mutations on both alleles of DNAH5 were identified in 15% of our clinically heterogeneous cohort of patients. Although genetic alterations remain to be identified in most patients, DNAH5 is to date the main PCD gene.